Enzyme‐like Supramolecular Iridium Catalysis Enabling C−H Bond Borylation of Pyridines with meta‐Selectivity. Issue 33 (1st May 2021) - Trouvé, Jonathan; Zardi, Paolo; Al‐Shehimy, Shaymaa; Roisnel, Thierry; Gramage‐Doria, Rafael
Abstract: The use of secondary interactions between substrates and catalysts is a promising strategy to discover selective transition metal catalysts for atom‐economy C−H bond functionalization. The most powerful catalysts are found via trial‐and‐error screening due to the low association constants between the substrate and the catalyst in which small stereo‐electronic modifications within them can lead to very different reactivities. To circumvent these limitations and to increase the level of reactivity prediction in these important reactions, we report herein a supramolecular catalyst harnessing Zn⋅⋅⋅N interactions that binds to pyridine‐like substrates as tight as it can be found in some enzymes. The distance and spatial geometry between the active site and the substrate binding site is ideal to target unprecedented meta‐selective iridium‐catalyzed C−H bond borylations with enzymatic Michaelis–Menten kinetics, besides unique substrate selectivity and dormant reactivity patterns. Abstract : An iridium‐based supramolecular catalyst has been designed to selectively recognize pyridine‐like derivatives via secondary Zn⋅⋅⋅N interactions. Owing to the distance between the substrate binding site and the active site as well as the geometrical constraints, meta ‐selective borylation reactions were accomplished displaying catalytic behaviors typically encountered in enzymes.